2007
DOI: 10.1111/j.1539-6924.2007.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

What Motivates Individuals to Protect Themselves from Risks: The Case of Wildland Fires

Abstract: This research investigates the cognitive perceptual process that homeowners go through when faced with the decision to protect themselves from the risk of wildfires. This decision can be examined by looking at the interaction between the integrated protection motivation theory-transtheoretical model and different levels of homeowners' subjective knowledge related to wildfire risks. We investigated the role of motivation, decision stages of risk readiness, and subjective knowledge on the number of risk-mitigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
194
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(202 citation statements)
references
References 31 publications
6
194
1
1
Order By: Relevance
“…PMT is primarily applied to explain people's decisions to partake in health risk mitigation behaviors [33,34] and disaster prevention [35][36][37]. A number of researchers have also applied PMT to explain pro-environmental behaviors.…”
Section: Protection Motivation Theory and Conceptual Idea Of The Studymentioning
confidence: 99%
“…PMT is primarily applied to explain people's decisions to partake in health risk mitigation behaviors [33,34] and disaster prevention [35][36][37]. A number of researchers have also applied PMT to explain pro-environmental behaviors.…”
Section: Protection Motivation Theory and Conceptual Idea Of The Studymentioning
confidence: 99%
“…flooding, wildfire, and seismic hazards) have revealed that cognitive threat appraisals are important for responses to natural hazards (e.g. Grothmann and Reusswig 2006;Martin, Bender, and Raish 2007;Terpstra and Lindell 2012). However, especially when coping appraisals are considered, threat appraisals are not always significant predictors (e.g.…”
Section: Threat Appraisalsmentioning
confidence: 99%
“…Bubeck et al 2013;Grothmann and Reusswig 2006;Martin, Bender, and Raish 2007;Terpstra and Lindell 2012). Notably, whereas self-efficacy, in accordance with PMT, has been found to be significantly related to responses, the importance of resourcerelated attributes for responses suggested in the PADM has not been confirmed (e.g.…”
Section: Coping Appraisalsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shift, inspired by both ideological and monetary reasons (Veldheer et al 2012), is visible in areas ranging from flood management (Kievik and Gutteling 2011) to crime prevention (van Steden, van Caem, and Boutellier 2011). While people are capable of taking protective measures (see Martin, Bender, and Raish 2007), and such investments can reduce damage by calamities considerably (Kreibich et al 2005), an essential prerequisite remains an individual's financial resources.…”
Section: Introductionmentioning
confidence: 99%